Potential Change of Spatial Accessibility to Health Services With the Opening of Private Streets in Shenzhen, China - Wenhao Yu; Tinghua Ai; Jingzhong Li; Min Yang; Yun Shuai (IEEE Access, 2018)
The spatial accessibility to urban health services is a key issue for urban environment and public health studies, especially among developing countries with explosive population growth and limited urban land space. Chinese cities have experienced rapid growth and obtained remarkable economic achievements in the last three decades, while this also brings out numerous urban planning problems, e.g., spatial access disparities to urban services. For this, the Chinese government worked out a new policy, community opening policy, for the improvement of urban accessibility through opening the private intra-community streets and increasing the spatial density of public street network. Although this policy has not been implemented yet, this paper aims at predicting the extent to which the community opening policy increases the spatial accessibility to health services at different places. This paper simulates the new system of street network and compares the results of the spatial accessibility of health services within the current and potential (planned) network systems. More specifically, the Delaunay triangulation skeleton model is constructed from geographic information system building footprints data for generating intra-community street segments; then, with adding these private streets to the existing inter-community street network, the two-step floating catchment area method based on the network path distance is employed to assess spatial accessibility to health services under both the current and potential urban contexts of Shenzhen, China. The results show that the impacts of the community opening policy on spatial accessibility of health services have spatial variations, and the most positively and negatively affected places are gathered together in the center area of the city.